2021
DOI: 10.1186/s12891-021-04920-3
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygous c.598_612del and c.1746-20C > G CAPN3 genotype cause autosomal recessive limb-girdle muscular dystrophy-1: a case report

Abstract: Background Autosomal recessive limb–girdle muscular dystrophy-1 (LGMDR1), also known as calpainopathy, is a genetically heterogeneous disorder characterised by progression of muscle weakness. Homozygous or compound heterozygous variants in the CAPN3 gene are known genetic causes of this condition. The aim of this study was to confirm the molecular consequences of the CAPN3 variant NG_008660.1(NM_000070.3):c.1746-20C > G of an individual with suspected LGMDR1 by extensive complementary DNA (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…Several in silico prediction programs (PolyPhen-2 [ 16 ], MutationTaster [ 17 ], SIFT [ 18 ]) were used to predict the functional effect as well as the genomic evolutionary rate profiling (GERP) [ 28 ] score. Segregation analysis was performed by Sanger sequencing [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several in silico prediction programs (PolyPhen-2 [ 16 ], MutationTaster [ 17 ], SIFT [ 18 ]) were used to predict the functional effect as well as the genomic evolutionary rate profiling (GERP) [ 28 ] score. Segregation analysis was performed by Sanger sequencing [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although we reported two novel pathogenic mutations in LGMD patients for the first time, the shortcoming of this study is that the influence of mRNA level after mutation is not further verified through appropriate experiments. DNA sequence variants affect pre-mRNA processing through exon skipping, cryptic splicing, intron inclusion, leaky splicing, and other methods [30]. Therefore, it is difficult to accurately predict the specific cause of pathogenicity by artificial intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…However, Mroczek et al (2022) showed that this variant is hypomorphic causing LGMDR1 when occurs in trans position with another pathogenic/likely pathogenic variant [ 26 ]. Many studies confirm that this variant is causal when occurs in the compound heterozygous state [ 25 , 27 , 28 ]. According to these findings, we can hypothesize that one of our patients, in whom compound heterozygous CAPN3: c.[700G > A];[1746-20C > G] variants together with heterozygous POLG likely pathogenic variant: c.2243G > C (p.Trp748Ser) were identified can be diagnosed with LGMDR1.…”
Section: Discussionmentioning
confidence: 99%